Analisis Akuntabilitas Pengelolaan Alokasi Dana Desa (ADD) Dalam Upaya Meningkatkan Pembangunan dan Pemberdayaan Masyarakat Pada Desa Lambou Darul Ihsan Kecamatan Bukit Malintang Kabupaten Mandailing Natal - Fadilah Dalimunthe; Mustapa Khamal Rokan; Nurwani Nurwani (Jurnal Akuntan Publik, 2023)
This research aims to determine the accountability of managing village fund allocations in an effort to increase development and community empowerment in Lambou Darul Ihsan Village, Bukit Malintang District, Mandailing Natal Regency. This research uses a descriptive qualitative approach methodology, data collection techniques in this research are interview, observation and documentation techniques. Based on the research results, it was found that accountability in the management of village fund allocation in an effort to increase development and community empowerment in Lambou Darul Ihsan village in 2022 has been implemented in accordance with Minister of Home Affairs Regulation No. 20 of 2018 starts from planning, implementation, administration and reporting, while at the accountability stage both technically and administratively it is good, but sometimes there are inhibiting factors in preparing the report because the management still lacks experience and limited education, but this can be overcome because of the District government always provide coaching.